Diversity of Waterbirds in the Mangrove Area of Syiah Kuala District, Banda Aceh - Ahmad Zidan Al Ghifari; Rizky Ahadi; Samsul Kamal; Elita Agustina; Riri Rahmadani Putri (Jurnal Biologi Tropis, 2026)
The diversity of bird species illustrates the range of species present across ecosystems, which is characterized by variations in morphology, behavior, ecological roles, and their adaptability to environmental conditions. In mangrove ecosystems, birds function as important biological components that contribute to maintaining ecological balance and overall system stability. This research was conducted to determine the diversity level and composition of water bird species in the mangrove area of Syiah Kuala District, Banda Aceh, in order to provide scientific information for conservation planning and sustainable ecosystem management. The study applied an exploratory survey method by carrying out direct observations at selected sampling points based on purposive sampling considerations. Fieldwork was conducted in December 2025 within the mangrove ecosystem of Syiah Kuala District, Banda Aceh. The collected data on water bird diversity were processed and analyzed using the Shannon–Wiener diversity index formula. The observation results recorded a total of 291 individual water birds, consisting of 10 species grouped into 5 families. The calculated diversity index value (H' = 2.010429) indicates a moderate diversity category. These findings demonstrate that the mangrove ecosystem in Syiah Kuala District still has the capacity to support biodiversity. Therefore, proper management and continuous conservation efforts are necessary to ensure the sustainability of this ecosystem.